Perancangan Pengalaman Pengguna Aplikasi Personal Shopper menggunakan Metode Human-Centered Design - Febryana Roma Uli Marpaung; Riswan Septriayadi Sianturi; Agi Putra Kharisma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
Personal shopper services or buying and selling services are systems individuals offer to "buy" something, which is then added a fee or fee for services, usually called a jastip fee. Many people like the business concept of this entrusted service. Someone who is traveling somewhere/traveling also takes advantage of this assigned service business because it is easier to do than online applications. Followers of the point-of-purchase service provider account who are interested in buying products can order the desired product from the point-of-purchase service provider. Furthermore, the delivery service provider can buy the ordered goods and then send them to the customer with additional purchase custody fees and shipping costs (Sugiarto, 2019). Personal shoppers need to prepare several things when offering their services. The delivery service provider must arrange the order list, order quantity details, order quantity restrictions, and delivery location. In addition, the number of social media followers also affects the running of the buying and selling service. The more the number of social media followers, the higher the level of order for buying and selling services. Based on the problems described above, the purpose of this research is to design a better user experience in using the personal shopper application using the Human-Centered Design method. This study involved several stages according to the HCD method. Evaluation of usability and user experience was carried out using the System Usability Scale (SUS) and a user experience questionnaire (UEQ). Usability test results in mobile application design produce the following results, namely 100% effectiveness, 0.092 goals per second, and a user satisfaction rating of 84 with a Good rating. They are testing the user experience using UEQ with the results of the attractiveness aspect of 2.05, clarity of 2.28, efficiency of 2.23, dependability of 2.00, stimulation of 2.09, and novelty of 1.56.